INSIGHTS INTO POST-MORTEM INTERVAL ESTIMATION: EXPLORING BIOLOGICAL MARKERS AND THEIR SIGNIFICANCE - Menon, Pooja V; Aravind, G.B (Journal of Forensic Medicine and Toxicology, 2025)
Accurately estimating the post mortem interval (PMI) is crucial in forensic investigations. Biological markers within the deceased offer a promising approach for PMI estimation. [...]